Pengembangan Instrumen Surveilans Ventilator-Associated Events (VAE) Berbasis Algoritme National Healthcare Safety Network (NHSN) - Ardhena Ekasari; Nursalam Nursalam; Tri Pudy Asmarawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to develop a Ventilator-Associated Events (VAE) surveillance instrument based on the National Healthcare Safety Network (NHSN) in the intensive care unit (ICU). The method used is Research and Development with stages including literature study, observation evaluation, validity and reliability testing, and focus group discussions (FGD). The research results show that the development of an NHSN-based VAE surveillance instrument in the ICU consists of two sheets, namely the first sheet (patient identity, minimum daily PEEP, and FiO2) and the second sheet (IVAC PVAP criteria). The I-CVI test result is 1.00, and the KR 20 test is 0.96, which means it is valid and reliable. In conclusion, developing an NHSN-based VAE surveillance instrument in the ICU can be applied in hospitals to refine Ventilator-Associated Pneumonia (VAP) surveillance. This can objectively detect complications from using a ventilator due to infection or non-infection. Keywords: Infection, Instruments, Surveillance, VAE, VAP